In vitro antimicrobial and antioxidant activity of leaves and aqueous extract of four medicinal plants with phytobiotic potential in animal production - Aroche, R.; Jiang, X.; Rodríguez, R.; Li, X.; Avellaneda, Carolina; Martínez, Y. (Cuban Journal of Agricultural Science, 2023)
The aim of this study was to evaluate the in vitro antimicrobial and antioxidant properties of leaves and aqueous extracts from four medicinal plants (Anacardium occidentale, Psidium guajava, Morinda citrifolia, and Moringa oleifera). Six bacterial strains were used in the study, and the minimum bactericidal concentration (MBC) was determined for leaves, while the minimum inhibitory concentration (MIC) and MBC were evaluated for aqueous extracts. Additionally, the in vitro antioxidant activity was measured using 1,1-diphenyl-2-picryl-hydrazyl, and secondary metabolites were identified and quantified by ultra-high-performance liquid chromatography. Results showed that A. occidentale and P. guajava had the highest antimicrobial activity against all bacterial strains, with A. occidentale and P. guajava also demonstrating the highest antioxidant activity. A. occidentale had a high concentration of quercetin 3-O-glucoside-7-O-rhamnoside, kaempeferol-7-O-glucoside, quercetin, caffeic acid, and cinnamic acid in its leaves. In conclusion, A. occidentale and P. guajava are the most effective plants in terms of in vitro antimicrobial and antioxidant activity in their leaves and aqueous extracts, while Moringa oleifera has good antioxidant activity but no bactericidal effect, and Morinda citrifolia has no antimicrobial or antioxidant effect. Keywords: antimicrobial activity, bactericidal, fine powder, leaves, secondary metabolite, antioxidant